THE MORPHEMIC STRUCTURE OF A LANGUAGE - Zokirova Malikaxon (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2024)
This article delves into the various types of morphemes and elucidates the distinctions between them. Additionally, it delves into the semantic structures of linguistic units, drawing parallels between words and morphemes as lexical entities. Morphemes, being integral components of words, are discussed in terms of their role within linguistic constructs. For instance, while some words comprise a solitary morpheme, others may consist of multiple morphemes. Through this exploration, the article aims to provide a comprehensive understanding of the nuanced components that contribute to language formation.